Side Effects of Neem Oil on the Midgut Endocrine Cells of the Green Lacewing Ceraeochrysa claveri (Navas) (Neuroptera: Chrysopidae) - Scudeler, E. L. [UNESP]; Santos, D. C. [UNESP] (Entomological Soc Brasil, 2014)
We described the ultrastructure of Ceraeochrysa claveri (Navas) midgut endocrine cells in larva, pupa, and adult, and evaluated the side effects of ingested neem oil, a botanical insecticide obtained from the seeds of the neem tree (Azadirachta indica), on these cells. During the larval period, C. claveri were fed (ad libitum) Diatraea saccharalis (F.) eggs treated with neem oil at concentrations of 0.5%, 1%, or 2%. Transmission electron microscopy showed that two subtypes of endocrine cells, namely granular and vesicular, occurred in the midgut epithelium during the three stages of the life cycle. Both cell types did not reach the midgut lumen and were positioned basally in the epithelium. The endocrine cells did not show extensive infoldings of the basal plasma membrane, and there were numerous secretory granules in the basal region of the cytoplasm. In the granular endocrine cells, the granules were completely filled with a dense matrix. In the vesicular endocrine cells, the main secretory products consisted of haloed vesicles. Ultrastructural examination indicated that only the granular endocrine cells exhibited signs of morphologic changes of cell injury present in all life cycle stages after the larvae were chronically exposed to neem oil by ingestion. The major cellular damage consisted of dilatation and vesiculation of the rough endoplasmic reticulum and the development of smooth endoplasmic reticulum and mitochondrial swelling. Our data suggest that cytotoxic effects on midgut endocrine cells can contribute to a generalized disruption of the physiological processes in this organ due to a general alteration of endocrine function.
Keywords: Cell injury; cytotoxicity; digestive system; transmission electron microscopy